2012
DOI: 10.1017/s1049023x12001069
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Participate in Disaster Management Among Indian Dental Graduates

Abstract: A high degree of willingness to provide assistance during disasters was observed among undergraduate dental students. High attitude coupled with low knowledge and behavior scores regarding disaster management was also observed. Gender was associated with attitude and behavior, and residence with behavior of respondents regarding disaster management. Including disaster management in dental curricula and involvement of dental professionals in disaster management might be crucial for disaster management in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 44 publications
2
17
2
Order By: Relevance
“…Rajesh et al, 30,31 but do not concur with those observed by Colvard et al 57 Low perceived effectiveness scores were observed in the present study, which are similar to that observed by Katz et al 21 and Rajesh et al 30,31 This might be due to the absence of any specific training initiatives for Indian GDPs in mitigation of disasters. 30,31 The respondents in the present study also reported higher attitude scores, which might indicate that they were interested in contributing effectively toward disaster management.…”
Section: Discussioncontrasting
confidence: 60%
See 4 more Smart Citations
“…Rajesh et al, 30,31 but do not concur with those observed by Colvard et al 57 Low perceived effectiveness scores were observed in the present study, which are similar to that observed by Katz et al 21 and Rajesh et al 30,31 This might be due to the absence of any specific training initiatives for Indian GDPs in mitigation of disasters. 30,31 The respondents in the present study also reported higher attitude scores, which might indicate that they were interested in contributing effectively toward disaster management.…”
Section: Discussioncontrasting
confidence: 60%
“…30,31 The respondents in the present study also reported higher attitude scores, which might indicate that they were interested in contributing effectively toward disaster management. Countries, such as the United States have taken definite strides in the process of integrating dentists in disaster management at various levels.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations